Methane emission, intake, digestibility, performance and blood metabolites in sheep supplemented with cupuassu and tucuma cake in the eastern Amazon - Budel, Juliana Cristina de Castro; Castro, Vinicius Costa Gomes de; Souza, Shirley Motta de; Nahúm, Benjamin de Souza; Barbosa, Antônio Vinicius Corrêa; Rodrigues, Laurena Silva; Berndt, Alexandre; Rennó, Luciana Navajas; Morais, Eziquiel de; Silva, Jamile Andrea Rodrigues da; Rodrigues, Thomaz Cyro Guimarães de Carvalho; Silva, André Guimarães Maciel e; et al. (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the effects of diets containing Cupuassu (Theobroma grandiflorum) and Tucuma (Astrocaryum vulgare Mart.) cakes on intake, digestibility, serum metabolites, performance and methane emission in confined sheep in the Amazon. Twenty-eight animals, Dorper-Santa Inês, castrated, were distributed in metabolic cages, in a completely randomized design, with four treatments and seven replications: 1. Control (C40), without Amazonian cake on it and with 40 g/kg of ether extract (EE) in the Total Dry Matter (TDM); 2. Cupuassu (CUP), inclusion of cupuassu cake and 70 g/kg of EE; 3. Tucuma (TUC), inclusion of tucuma cake and 70 g/kg of EE; and 4. Control (C80), without addition of Amazonian cake and with 80 g/kg of EE, in the roughage:concentrate ratio of 40:60. The two cakes showed effects on intake, performance and methane emission (P < 0.05). The inclusion of tucuma cake reduced the dry matter (758 g), crude protein and ether extract intake, when compared to the inclusion of cupuassu cake; on the other hand, increased neutral detergent fiber intake. Higher averages of DM and CP digestibility occurred in C40 (P < 0.05), while in the TUC there was the highest digestibility of NDF. Serum concentrations of metabolites: glucose, total cholesterol, triglycerides and HDL were influenced by diets (P<0.05), however, no effect was observed on the variables protein and albumin (P>0.05). Sheep that received CUP and TUC had lower daily weight gains than those fed with diets without cakes inclusion. Methane emission was lower in animals fed TUC (26 L/day) and higher in C40 (35 L/day), however the TUC provided higher methane emission in g/BW gain per day (353 g/BW/day). Thus, supplementation with cakes did not reduce the enteric methane emission in confined sheep in the Amazon, however, the use of cupuassu cake is a sustainable strategy, as it showed similar results to the Control methods and did not contribute to increase methane emission, as occurred with the inclusion of tucuma cake.